Servant Leadership Competencies Development Challenges for Middle Managers in the Organisation - Supranavičienė, Ugnė; Gedvilienė, Genutė (Acta Paedagogica Vilnensia, 2024)
The perception and identification of leadership are continuously being researched. However, in recent times the need for leadership has become more apparent in organisations of all kinds. The everyday reality of the present day is forcing us to rethink all the truths and theories of leadership that have been defended so far. This paper aims to reveal the challenges of middle managers in organisation towards servant leadership competencies development. A qualitative research design was used to explore the competencies of middle managers. Data was collected from seven middle managers in one of the Lithuanian Railways organisation LTG Link. These managers participated in three competency development assessments (self-confidence, emotional intelligence and leadership assessments), following focus group discussion where they were reflected on leadership concepts in the organisation, how they perceive themselves in the organisation, how they recognise servant leadership competencies and what challenges are facing in order to bring servant leadership as a dominant leadership style in the organisation. Managers were asked to reflect in three competency development layers: the reflection of middle managers’ understanding of leadership and management; understanding of the relationships between middle managers and subordinates; and understanding of relationships between middle managers and their management. According to the research findings, there are challenges in all the layers for middle managers to develop servant leadership competencies. Current leadership conception in the organisation is focused on a manager-centric approach, where the main focus is on the manager not the subordinate, in the servant leadership concept there is an employee-centric approach. The organisation’s processes and procedures are constructed to control and constrain the decision-making of middle managers. There is no working competency development and support system in the organisation to guide middle managers to become servant leaders, this leads to a nonunified leadership competency concept in the organisation, where middle managers bring their own understanding without any background. Furthermore, the hierarchical organisational structure limits the motivation of middle managers to develop their servant leadership competencies.
Keywords: adult education; competencies; leadership challenges; middle managers; servant leadership